2022
DOI: 10.1038/s41587-022-01489-7
|View full text |Cite
|
Sign up to set email alerts
|

Extending fluorescence anisotropy to large complexes using reversibly switchable proteins

Abstract: The formation of macromolecular complexes can be measured by detection of changes in rotational mobility using time-resolved fluorescence anisotropy. However, this method is limited to relatively small molecules (~0.1–30 kDa), excluding the majority of the human proteome and its complexes. We describe selective time-resolved anisotropy with reversibly switchable states (STARSS), which overcomes this limitation and extends the observable mass range by more than three orders of magnitude. STARSS is based on long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Hence, the presence of distinct Arc n -meric states may be necessary to support functions, such as receptors endocytosis, cytoskeletal binding or viral-like interneuronal transfer. In different heterologous systems, we 23 and Hedde et al, 24 have demonstrated that Arc forms, together with monomeric and low-order oligomers, rigid nanometric particles. In primary cortical neurons and in rat dentate gyrus 25 , Arc was reported to form low-abundance dimers and low-order oligomers (trimers, tetramers), which increase upon plasticity induction.…”
Section: Introductionmentioning
confidence: 74%
“…Hence, the presence of distinct Arc n -meric states may be necessary to support functions, such as receptors endocytosis, cytoskeletal binding or viral-like interneuronal transfer. In different heterologous systems, we 23 and Hedde et al, 24 have demonstrated that Arc forms, together with monomeric and low-order oligomers, rigid nanometric particles. In primary cortical neurons and in rat dentate gyrus 25 , Arc was reported to form low-abundance dimers and low-order oligomers (trimers, tetramers), which increase upon plasticity induction.…”
Section: Introductionmentioning
confidence: 74%
“…Interestingly, the slopes decrease monotonically with increasing LiCl, suggesting the hydrodynamic volume, V , of perylene to decrease with increasing LiCl concentration in glyceline. 40,41 LiCl appears to detach the H-bond networked DES around the probe perylene, which makes the hydrodynamic volume smaller. This would result in a change in the cybotactic region viscosity ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Here we made steady-state measurements, considering only quasi-static fluorescent reporters. Time-resolved orientation measurements provide a large set of possibilities for this field [56, 57], and combining time-resolved measurements with reversibly switchable proteins allows measurement of a wide range of reorientation timescales [58], giving access to reorientation timescales of large protein complexes. We are excited for future developments that probe long-timescale reorientation of fluorophores trapped in 3D angular potentials.…”
Section: Discussionmentioning
confidence: 99%